CONTRIBUTION OF THE ROLE OF SOCIAL CAPITAL IN THE DEVELOPMENT OF RURAL COMMUNITIES - Firdaus W Suhaeb; Ernawati Syahruddin Kaseng (Universitas Negeri Makassar, 2023)
The study of this article aims to illustrate the importance of social capital in community development in rural areas assuming that social capital energy still exists in community life in rural areas today but certainly needs to be improved sustainably. Using the method of literature study, so that the secondary databases obtained are compiled, analyzed and inferred. The data collection stage is through taking data from the library, reading, recording, and then processing the data from the materials obtained. The results of the study show that through the elements of social capital owned by the community in rural areas, the role of social capital can contribute to increasing community productivity, social development, economic development as well as the development and rehabilitation of various village infrastructures in a mutual cooperation. Social exchanges that are built in rural communities that tend to be based on certain motives including because there are certain motives of profit, interests and rewards, are intertwined through interlocking social networks. This is also supported by the existence of social values and norms in the culture of the village community. For this reason, a sustainable increase in social capital in rural communities is expected to improve the economy and reduce poverty in addition to the increase in various other development sectors in rural areas today.